The effect of digital marketing communications on Adit Sopo Jarwo's animation brand awareness and brand reputation through children's educational content - Permana, Aditya; Kholisoh, Nur (Bricolage : Jurnal Magister Ilmu Komunikasi, 2023)
Indonesian animation should be able to compete with foreign animation, but in fact the broadcast of Indonesian animation in Indonesia is still inferior, especially on national television. To keep up with overseas animation, especially in the national market, there needs to be a creative strategy in marketing these local animations to increase brand awareness and a good brand reputation so that Indonesian animation can be a major choice for animation shows, as MD Animation does by utilizing the technology. Social media is a means of presenting educational content to children to increase the brand awareness and reputation of their product, the Adit Sopo Jarwo animation. This study aims to find out the effect of digital marketing communication on Adit Sopo Jarwo's brand awareness and animation reputation through child education content, a survey was conducted on followers of @mdanimation's Instagram account. In this study, the theory used is digital marketing communication theory, brand awareness, brand reputation and stimulus, organism, and response (SOR) theory, which is to see how the response from the audience affects brand reputation. This study used a positivist paradigm with a quantitative approach and used survey research methods and data analysis techniques using path analysis. The samples used in this study were 387 respondents with sample determination using purposive sampling. The results of this study were obtained in that digital marketing communication was shown to have a direct and significant influence on brand reputation. In addition, the results of the analysis with the Sobel test show the influence of the brand awareness variable as an intervening variable between the digital marketing communication variable and the brand reputation, so it can be said that the indirect effect or indirect influence is significant.